An integrated, systems-wide approach is needed for public-private partnerships to drive genetic innovation in crops. - Catherine Feuillet; Kellye Eversole (PLoS Biology)
Public-private partnerships are key to successfully translate knowledge to products, but current frameworks do not foster the systems-wide approach required to improve crops to meet the agricultural production challenges of the 21st century.